Membangun Integritas Pendidikan Etika Dalam Konsep Islam - Slamet Pujiono (LP2M STIT Al-Hikmah Way Kanan, 2020)
Progress and glory in the future is very much determined by the development of the Muslim community itself. Religion can be made as a supporting and supporting factor for the development process. In rebuilding the integrity of this nation, improvements are needed in various fields of life, especially in the field of ethical education. Through the world of education and social life arrangements for future generations. Ethical issues are inseparable from the role of religion as its controller. Religion is a source of motivation for development, which is a factor that can encourage and inspire people and society to develop. Ethics Education in the concept of Islam has been practiced by the Prophet as Uswah Khasanah for all people. Good ethical education exists in religion because ethical values ​​are obeyed from self-awareness. Islam as a guide to human life and to provide solutions to various humanitarian problems. Among them are issues of social ethics of brotherhood and peace. Ethics and morality are the pinnacle of the religious value of a Muslim. The role of ethics education in empowering development is very important, it requires reforms of all components of education starting from the macro level to the individual level. Education must be able to develop an ethical and moral young generation in accordance with the ideals of the nation, state and religion.